Accounting and Corporate Reporting Today and Tomorrow - Gokten, Soner (IntechOpen, 2017)
We have spent a great deal of time on the continued development of accounting and auditing standards, which are used as a primary component of corporate reporting, to reach today's financial reporting framework. However, is it possible to say that, currently, financial statements provide full and prompt disclosure? Or will they still be useful as a primary element with their current structures in corporate reporting? Undoubtedly, we are deeply concerned about these issues in recent times. This volume contains chapters to discuss the today's and tomorrow's accounting and corporate reporting phenomena in a comprehensive and multidimensional way. Therefore, this book is organized into six sections: "Achieving Sustainability through Corporate Reporting", "International Standardization", "Financial Reporting Quality", "Accounting Profession and Behavioral Aspects", "Public Sector Accounting and Reporting", and "Managerial Accounting".